2019
DOI: 10.1016/j.atmosenv.2018.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Global changes in the diurnal cycle of surface ozone

Abstract: A B S T R A C TChanging emissions of NO x and other ozone precursors drive trends in both production and loss of surface ozone, leading to surface ozone trends that differ according to the time of day. Consequently, the magnitude of the diurnal cycle in surface ozone is changing in several regions of the world. Changes in the diurnal cycle of ozone have implications for the metrics used to assess the impact of ozone on human health and vegetation, since different metrics are sensitive to different portions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 52 publications
1
62
0
Order By: Relevance
“…The M2 GMI Replay near‐surface high bias permeates all latitudes (Figure a); there is a high bias at every site except Watukosek, one of the few tropical sites that exhibit frequent surface O 3 pollution. This high bias was also noted in Strode et al (), who found that M2 GMI Replay high biases were largest during the nighttime (the vast majority of sonde data are during the daytime). Near‐surface biases in GMI CTM O 3 are much closer to zero (Figure b), with the largest negative bias also found at Watukosek.…”
Section: Model Biases and Correlations With Ozonesondessupporting
confidence: 78%
“…The M2 GMI Replay near‐surface high bias permeates all latitudes (Figure a); there is a high bias at every site except Watukosek, one of the few tropical sites that exhibit frequent surface O 3 pollution. This high bias was also noted in Strode et al (), who found that M2 GMI Replay high biases were largest during the nighttime (the vast majority of sonde data are during the daytime). Near‐surface biases in GMI CTM O 3 are much closer to zero (Figure b), with the largest negative bias also found at Watukosek.…”
Section: Model Biases and Correlations With Ozonesondessupporting
confidence: 78%
“…For example, two CTM-based studies estimated 2005 respiratory-related premature mortalities in the USA using the same relative risk function (Jerrett et al, 2009), yet yielded results that differed by ∼ 3× (i.e., 13 000 vs. 38 000; Zhang et al, 2018;Lelieveld et al, 2013). While CTMs accurately reproduce many features of atmospheric chemistry (Shindell et al, 2013;Hu et al, 2018), one important issue associated with CTM-based impact assessments is that CTMs are consistently biased high when predicting O 3 concentrations (e.g., Schnell et al, 2015;Travis et al, 2016;Yan et al, 2016;Seltzer et al, 2017, Porter et al, 2017Guo et al, 2018). Such biases can influence estimates of impacts and are often amplified by nonlinear concentrationresponse functions .…”
Section: Introductionmentioning
confidence: 99%
“…Total ozone levels vary from year to year, depending on the dynamical state of the global atmosphere mainly determined by El Niño-Southern Oscillation (ENSO) and the Quasi-Biennial Oscillation (QBO). Both ENSO and the QBO are tropical phenomena that have a strong influence on the Brewer-Dobson circulation (BDC) determining the global stratospheric ozone distribution (e.g., Diallo et al 2018;Olsen et al 2019). Throughout 2019, the QBO was in its west phase, which generally leads to higher total ozone in the inner tropics and lower ozone in the subtropics and beyond (Plate 2.1z).…”
Section: )mentioning
confidence: 99%
“…Throughout 2019, the QBO was in its west phase, which generally leads to higher total ozone in the inner tropics and lower ozone in the subtropics and beyond (Plate 2.1z). The extended regions of below-average total ozone at low to middle NH latitudes are possibly linked to the weak ENSO condition in 2019 (Olsen et al 2019). A major feature of 2019 is the very weak stratospheric SH winter polar vortex, a very small ozone hole (see Sidebar 6.1), and above-average total ozone at high southern latitudes during austral winter/spring as well as in the annual mean (Plate 2.1z).…”
Section: )mentioning
confidence: 99%